Voltage Swells Improvement in Low Voltage Network Using Dynamic Voltage Restorer - Omar, Rosli; Rahim, Nasrudin; Ahmad, Azhar (Science Publications, 2011)
Abstract: Problem statement: Voltage disturbances are the most common power quality problem due to the increased use of a large numbers of sophisticated electronic equipment in industrial distribution system. The voltage disturbances such as voltage sags, swells, harmonics, unbalance and flickers. High quality in the power supply is needed, since failures due to such disturbances usually have a high impact on production cost. There are many different solutions to compensate voltage disturbances but the use of a DVR is considered to be the most cost effective method. The objective of this study is to propose a new topology of a DVR in order to mitigate voltage swells using a powerful power custom device namely the Dynamic Voltage Restorer (DVR). Approach: New configuration of a DVR with an improvement of a controller based on direct-quadrature-zero method has been introduced to compensate voltage swells in the network. Results: The effectiveness of the DVR with its controller were verify using Matlab/Simulink’s SimPower Toolbox and then implemented using 5KVA DVR experimental setup. Simulations and experimental results demonstrate the effective dynamic performance of the proposed configuration. Conclusion: The implimentation of the proposed DVR validate the capabilities in mitigating of voltage swells effectiveness.During voltage swells, the DVR injects an appropriate voltage to maintain the load voltage at its nominal value.